Kneeling after Total Knee Arthroplasty - Amin, Raj M.; Vasan, Vikram; Oni, Julius K. (The Journal of Knee Surgery, 2020)
The ability to kneel is one of the many patient goals after total knee arthroplasty (TKA). Few studies have addressed patients' ability to kneel after TKA as a primary outcome. Given the altered biomechanics of the knee after TKA, the various implant designs, and multiple surgical approaches, there is a need to further understand the patient's kneeling ability after TKA. We evaluated the available literature on this topic to help to guide postoperative care recommendations. Biomechanical data show that the load borne by the patellofemoral joint is elevated significantly at all flexion angles, whereas tibiofemoral articulation pressures are elevated only at 90 to 120 degrees of flexion. However, these increased pressures are rarely borne by prosthetic knees because patients often avoid kneeling after TKA. In patients who do kneel after surgery, data show that increased range of motion promotes improved kneeling performance. Targeted interventions to encourage kneeling after TKA, including preoperative education, have not shown an ability to increase the frequency with which patients kneel after TKA. Reasons for patient avoidance of kneeling are multifaceted and complex. There is no biomechanical or clinical evidence contraindicating kneeling after TKA. There are insufficient data to recommend particular prosthetic designs or surgical approaches to maximize kneeling ability after surgery. Musculoskeletal health care providers should continue to promote kneeling to allow patients to achieve maximum clinical benefit after TKA.
Keywords: deep flexion; double-stance kneeling; kneeling; outcomes; total knee arthroplasty; single-stance kneeling